Design And Construction Of Small Scale Plastic Injection Molding Machine Using High-Density Polyethylene (HDPE) Material - Hau, Fikarahman Putra; Muharom, Muharom; Setyono, Gatot; Khusna, Dwi; Kholili, Navik (Journal of System Engineering and Technological Innovation, 2024)
Injection molding has become a significant manufacturing technique in producing complex polymer components. Its molding efficiency depends on various process and machine parameters, which determine the quality of the final product in terms of various output responses. It is important to state that proper optimization of different input parameters is essential to achieve the desired quality index. This article presents a review of various techniques used so far to optimize various injection molding parameters, along with their advantages and limitations. It is found in the review that a brilliant technique that can be operated without human intervention has not been developed. The design of the injection machine uses a small scale between 75 gr to 150 gr with a heating variation ranging from 200 0C to 250 0C. When testing the tool, it showed that to achieve the optimal final result of a product, it takes 228 seconds at a hot temperature of 200 0C; if the temperature is increased to 225 0C, it takes 217 seconds, and if it is increased to 250 0C, it takes a shorter time of 208 seconds.